2008
DOI: 10.1016/j.exer.2008.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Sub-retinal drusenoid deposits in human retina: Organization and composition

Abstract: We demonstrate histologically sub-retinal drusenoid debris in three aged human eyes, two of them affected by age-related maculopathy. By postmortem fundus examination, the lesions appeared drusen-like, i.e., they were pale spots apparently at the level of the retinal pigment epithelium (RPE). Light and electron microscopy revealed aggregations of membranous debris, the principal constituent of soft drusen, in the sub-retinal space. Immunohistochemistry and confocal microscopy confirmed the presence of molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
173
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 28 publications
5
173
1
1
Order By: Relevance
“…RPD however do differ from drusen in some constituents, and have low levels of apoB, apoA-I, and esterified cholesterol, thought to represent components of an RPEproduced lipoprotein (Li et al, 2006). RPD were also thought to lack immunoreactivity for photoreceptor, Müller cell, and RPE marker proteins (Rudolf et al, 2008b). However Sarks et al have identified components of disorganized and undigested photoreceptor outer segment in the same specimens as RPD (Sarks et al, 2011).…”
Section: Compositionmentioning
confidence: 96%
See 1 more Smart Citation
“…RPD however do differ from drusen in some constituents, and have low levels of apoB, apoA-I, and esterified cholesterol, thought to represent components of an RPEproduced lipoprotein (Li et al, 2006). RPD were also thought to lack immunoreactivity for photoreceptor, Müller cell, and RPE marker proteins (Rudolf et al, 2008b). However Sarks et al have identified components of disorganized and undigested photoreceptor outer segment in the same specimens as RPD (Sarks et al, 2011).…”
Section: Compositionmentioning
confidence: 96%
“…These include the presence of membranous vesicles, membrane-bounded particles with neutral lipid interiors, unesterified cholesterol (UC), apolipoprotein E (apoE), complement factor H, and vitronectin (Rudolf et al, 2008b). The same material has also been identified enclosed within RPE intracellular vacuoles and so it has been suggested that these vacuoles eventually release their contents, forming conventional drusen at the basolateral RPE surface or RPD if released from the apical surface (Curcio et al, 2013;Curcio and Millican, 1999;Curcio et al, 2005;Sarks et al, 1988;Sarks et al, 2007).…”
Section: Compositionmentioning
confidence: 99%
“…4 Recently, it was shown by spectral-domain optical coherence tomography (SD-OCT) and histopathology that reticular pseudodrusen are accumulations of material that are above the RPE, in the subretinal space, and therefore were named subretinal drusenoid deposits. 5,6 However, subretinal drusenoid deposits can look similar in color fundus photography to cuticular drusen and might be mistaken for cuticular drusen. Through the development of enhanced imaging modalities, especially the advent of SD-OCT, ideas about drusen [4][5][6][7] This report describes the association of vitelliform detachment in adults with subretinal drusenoid deposits using multimodal imaging.…”
Section: Acquired Vitelliform Detachment In Patients With Subretinal mentioning
confidence: 99%
“…5,6 However, subretinal drusenoid deposits can look similar in color fundus photography to cuticular drusen and might be mistaken for cuticular drusen. Through the development of enhanced imaging modalities, especially the advent of SD-OCT, ideas about drusen [4][5][6][7] This report describes the association of vitelliform detachment in adults with subretinal drusenoid deposits using multimodal imaging. In each patient, 31 to 37 B-scans were obtained within a 20°x 25°or 30°x 25°rectangle to encompass the macula, including the area between the temporal arcades.…”
Section: Acquired Vitelliform Detachment In Patients With Subretinal mentioning
confidence: 99%
See 1 more Smart Citation